Evidence-based planning. Rhetoric and reality. - Davoudi, Simin (TH Zürich, NSL, 2006)
Der Beitrag arbeitet Varianten wissenbasierter Planung am Beispiel Großbritanniens heraus. Die instrumentelle Variante, wie sie das Weißbuch über die Verwaltungsmodernisierung verwendet, basiert auf drei Mißverständnissen über die Natur des Wissens, die Rolle von Experten und über den Einfluss, den sie auf auf politisches Handeln haben. Anhand von Beipielen aus der Planungspraxis in Großbritannien wird gezeigt, wie weit Wissen und Wissensanwendung in der idealen und der wirklichen Welt auseinanderfallen. Außerdem wird auf Ähnlichkeiten der heutigen Begeisterung für wissensbasierte Planung mit der auf überdetailierten Statistiken beruhenden Planungsversessenheit der 1960er und 1970er Jahre hingewiesen. goj/difu

This paper aims to conceptualize the upsurge of government interest in evidence based policy in Britain by drawing on two models of policy-evidence interface; the instrumental and the enlightenment model. It argues that much of the drive behind the enthusiasm for evidence is rooted in the linear and utilitarian view of research which is broadly based on three interrelated misconceptions about the nature of evidence, the role of experts, and the influence that these can have on policy. By drawing on examples from the UK planning systems, the paper explores the mismatch between the use of evidence in the "ideal" and the "real" worlds of planning and policy process. It is argued that the assumption made under the positivist view of planning in the 1960s and 1970s are similar to those made under the instrumental view of the policy-research interface. difu difu
Keywords: Raumordnung; Raumordnungspolitik; Raumplanung; Raumstruktur; Planungstheorie; Planungspraxis; Planungsgeschichte; Planungswissenschaft; Wissensanwendung; Governance